2015
DOI: 10.4236/jdm.2015.51004
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Insulin Glulisine in Intensive Insulin Therapy: Bolus Insulin Adjust Nice Control by apiDRA Study (BANDRA Study)

Abstract: Background: Treatment for postprandial glycemia using rapid-acting insulin analogues sometimes resulted in preprandial hypoglycemia or weight gain. Objective: This study evaluated the efficacy and safety of switching bolus insulin from insulin lispro (Lis) to insulin glulisine (Glu) in patients with inadequately controlled diabetes on intensive insulin therapy with Lis and glargine (Gla). Methods: Seventy-two outpatients with inadequate glycemic control (glycated hemoglobin [HbA1c] ≥ 7.0%, glycated albumin [GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…An improved glycaemic control after switching from insulin lispro to insulin glulisine has also been reported by a study performed in Japan (BANDRA) [ 6 ], where patients with different diabetes types experienced a reduction of the HbA1c from 8.26 to 7.71% (66.8–60.8 mmol/mol; p < 0.01) using a glulisine titration algorithm. Furthermore, Yanagisawa et al [ 7 ] reported on the outcomes of a study in 49 T1DM and 10 T2DM patients whose treatment was switched from basal insulin in combination with aspart, lispro or regular human insulin to a combination of basal insulin and insulin glulisine.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…An improved glycaemic control after switching from insulin lispro to insulin glulisine has also been reported by a study performed in Japan (BANDRA) [ 6 ], where patients with different diabetes types experienced a reduction of the HbA1c from 8.26 to 7.71% (66.8–60.8 mmol/mol; p < 0.01) using a glulisine titration algorithm. Furthermore, Yanagisawa et al [ 7 ] reported on the outcomes of a study in 49 T1DM and 10 T2DM patients whose treatment was switched from basal insulin in combination with aspart, lispro or regular human insulin to a combination of basal insulin and insulin glulisine.…”
Section: Discussionsupporting
confidence: 62%
“…This was likely due to the lower number of patients with T1DM ( n = 40) compared to T2DM ( n = 304). Both the introduction of insulin glulisine [ 6 , 7 ] and its up-titration upon a switch [ 6 ], as well as the performance of a 7-point blood glucose profile [ 11 , 12 ], have been demonstrated to improve glycaemic control in patients with diabetes. As such, these two changes to patient care likely contributed to the observed effects on glycaemic control and potentially should be implemented in parallel in practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation